PENGARUH INFLUENCER, CONTENT MARKETING, DAN EFEKTIVITAS MEDIA TIKTOK TERHADAP KEPUTUSAN PEMBELIAN SABUN KOJIE SAN - Agustin Tanjung; Dae Sinka Romenda (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The beauty business is currently growing rapidly and is becoming increasingly diverse, one of which is beauty or skin care products. Skin care is now starting to appear and causing increasingly fierce competition among manufacturers. The purpose of this study was to determine the effect of influencers, content marketing, and the effectiveness of Tiktok on purchasing decisions for Kojie San soap. The research method used is quantitative with a total sample of 323 respondents. The data collection technique used is a questionnaire. The sampling method used was non-probability sampling with purposive sampling technique. The data analysis method was multiple linear regression analysis. The results of this study show that the independent variables of influencers, content marketing and the effectiveness of the tiktok media have a significant effect on the dependent variable, namely purchasing decisions. The value of Adjusted R Square shows several 0.838 which means that this variable contributes 83.8% to the purchaing decision of Kojie San soap. Partially, Content marketing and the Effectiveness of Tiktok have a significant effect on purchasing decisions Kojie San soap.